Student Camps to Promote Scientific Vocations in STEM: The Quimi Camp Case - Sandoval-Barrantes, Manuel (2023)
[Objective] From 1988 to 2018, high school students in Costa Rica had to pass a final exam to graduate from high school and be eligible for public university education. In this context, students had to choose a national science test from the areas of physics, chemistry, and biology. Historically, chemistry was the least chosen (4-6 %) of those sciences. On the other hand, there is a need -at the national level- to increase interest in careers related to STEM (Sciences, technology, engineering, and mathematics). [Methodology] Under both premises, in 2016, the first national camp (called Quimi Camp) to promote scientific vocations was held to encourage high school students in Costa Rica to choose chemistry. Quimi Camp is an event supported by the OLCOQUIM National Chemistry Olympiad and the OLCOCI National Science Olympiad, which are in turn organized by the five Costa Rican State universities and the LANOTEC CENAT National Nanotechnology Laboratory at the National Center of High Technology, with the consent of the Ministry of Education (MEP) and the Ministry of Science, Innovation, Technology and Telecommunication (MICITT). The participating students made the final evaluation of this event. [Results] The results showed an excellent perception of the event regarding its organization and content. [Conclusions] Quimi Camp promoted students' vocation for science and engineering and positively influenced the selection of a University Career in STEM.